Designing gabor-filter for image texture using VHDL / Mohd Faizul Md Idros, Adizul Ahmad and Abdul Hadi Abdul Razak - Md Idros, Mohd Faizul; Ahmad, Adizul; Abdul Razak, Abdul Hadi (Research Management Institute (RMI), 2012)
Just as an idea from image sensing technology, we can clarify any type of image after digitized it. Possibility, in the future we can determine the colour, material and size of the real image. This technology mainly can be applied in forensic and biometric for investigation such as finger print and face identification. In real world, the investigation of finger prints and face identification takes a long time because of our limited technology. There are a lot of software can be use to build a new system of fingerprint and face identification like Matlab, Neural Network, Fuzzy logic and many others. But the software can't stand alone and need to connect to computer. Because of this problem, we propose to implement the image texturing by using Garbor filter and implement it on the FPGA. Soon after this research completed, we can produce a new Integrated Circuit that can be use in forensic and also biometric area. This project aim is to design Gabor Filter in image recognition system segment the texture. Texture segmentation is the process of partitioning an image into regions based on their texture. The reason using Gabor filter is due to it characteristic. This system design is intended to enhance the efficiency of existing technology. The scope of this research is to make the system know the different type of image and it can be expand until can determine the material of the real image. The applications of this image sensing are user convenience (e.g. money withdrawal without ATM card and PIN), better security and automotive industry also can use this image sensing technology as the security or comfort purpose. As a conclusion the number of biometric products on the market is multiplying rapidly.